Effects of Intrathecal Sufentanil on Plasma Oxytocin and Cortisol Concentrations in Women During the First Stage of Labor. Issue 6 (1st November 2001) - Stocche, Renato M.; Klamt, Jyrson G.; Antunes-Rodrigues, José; Garcia, Luis V.; Moreira, Ayrton C.
Abstract : Background and Objectives: Intrathecal sufentanil provides analgesia comparable to epidural bupivacaine for the first stage of labor. Both epidural local anesthetics and intrathecal opioid reduce some parameters of the neuroendocrine response to labor pain and the reflex release of oxytocin in animals. In humans, epidural local anesthetics only reduce the spurt release of oxytocin. This study compared the effect of intrathecal sufentanil and epidural bupivacaine administration on the plasma concentration of oxytocin and cortisol in women with labor pain during the first stage of labor. Methods: Thirty healthy parturients requesting analgesia were enrolled in this randomized and open-label study. Each patient was in spontaneous labor at greater than 5 cm cervical dilatation. Using a combined spinal and epidural technique, patients received either intrathecal sufentanil 10 μ g (SUF = intrathecal sufentanil group) or epidural plain bupivacaine 0.25%, 12 mL (BUPIV = epidural bupivacaine group). Analgesia was assessed using a visual analog scale, and blood samples for oxytocin and cortisol plasma concentration measurements were collected immediately before analgesia and 15, 30, 60, and 90 minutes after induction of the analgesia. Plasma cortisol and oxytocin concentrations were determined by specific radioimmunoassay. The values were expressed as mean ± SEM. Results: Intrathecal sufentanil provided faster and more complete analgesia within 15 and 30 minutes of its administration, compared with epidural bupivacaine. Plasma oxytocin concentrations were similar in the 2 groups before analgesia (7.24 ± 2.1 and 6.6 ± 3.1 pg/mL SUF and BUPIV, respectively). It decreased significantly in the SUF and increased in the BUPIV after analgesic administration. Cortisol concentrations were elevated in both groups before analgesia (51.6 ± 5.3 and 54.2 ± 4.8 μ g/dL SUF and BUPIV, respectively). Both analgesic treatments significantly decreased the plasma cortisol levels. Conclusions: Intrathecal sufentanil analgesia decreases plasma concentrations of oxytocin and cortisol in women with labor pain during the first stage of labor, but epidural bupivacaine only reduced the cortisol concentration.